(untitled) (International Journal of Food and Nutritional Sciences, 2023)
This study presents an innovative Internet of Things-based project aimed at simplifying and automating the process of plant watering, with a special emphasis on meeting the unique needs of the elderly. To enable efficient monitoring and administration of watering activities, the system includes a variety of components, including sensors, a microcontroller, and an easy-to-use mobile application. The primary purpose of this system is to provide an accessible and user-friendly solution for elderly people to cultivate healthy plants without the physical effort that has traditionally been associated with this task.This study addresses the widespread problem of plant neglect among the elderly, providing a straightforward way for them to actively participate in gardening while ensuring their plants receive maximum care. This research represents a huge step forward in fostering independence and active involvement among senior gardeners, demonstrating the potential of IoT technology to improve their gardening experience.